Conflicts concerning construction projects under the challenge of cleaner production – case study on government funded projects. (10th July 2019) - Wang, Nannan; Ma, Minxun; Wu, Guobin; Liu, Yunfei; Gong, Zheng; Chen, Xiaoyan
Abstract: Although the construction industry is an important economic pillar for a nation, and contributes greatly to the improvement of the citizens' standards of living; it is criticized for intensive pollution and resource consumption during the operational process of construction projects. The stricter regulations of the government and the raising awareness of public on environmental protection bring more challenge and conflict to government funded construction projects for cleaner production. This research intends to investigate the conflicts the construction projects experienced in the changing social and political environment, and how the project teams resolve these conflicts. Through multiple case studies on six government funded projects, there are 17 types of conflict identified, linking to six groups of external stakeholders of the government funded projects. The causes and solutions of the conflicts are discussed with the help of site observation, document review and interview survey. Strategies and suggestions are provided for conflict management of government funded projects. The findings will benefit researchers and practitioners involved in construction industry by providing better perception and management of conflicts, therefore to promote cleaner production. Highlights: The construction projects are found facing new challenges under the increasing requirement on cleaner production. Exploring conflict of construction projects with external stakeholders in the changing environment of China. Causes and resolution strategies for conflicts revealed for improving the project performance in cleaner production.